Sparental Parenting Strategies in Resilience in Disaster Survivors Aged 7-12 Years in Lere Huntara - Alimuddin, Nurwahida; Rahmi, Sitti (Journal International Dakwah and Communication, 2024)
Parents play a crucial role in their children's lives, providing support in both joyful moments and challenging situations, such as the post-disaster conditions currently experienced by families in Lere Huntara. In such circumstances, effective parenting strategies are essential to help child survivors build resilience, enabling them to adapt and accept their current situation without being overwhelmed by it. However, findings from this study indicate that parents in Lere Huntara lack specific parenting strategies to foster resilience in their children. This is largely due to environmental limitations, including inadequate living conditions and the lack of proper play facilities for children. As a result, many parents in the refugee camp become more neglectful in their approach to raising their children, unintentionally hindering their emotional and psychological development. This research employs a qualitative approach, utilizing data collection techniques such as verbatim transcription, tabulation, and documentation. The study specifically focuses on parenting strategies for child survivors aged 7-12 years in Huntara Lere. The research subjects consist of parents residing in Lere Village, West Palu District, Palu City, where the disaster impact was particularly severe. The implications of this research highlight the urgent need for parents to adopt appropriate parenting strategies tailored to the needs of child survivors. By providing proper guidance and emotional support, parents can help their children develop resilience, ensuring they are better equipped to cope with the challenges posed by the disaster.